The Contribution of the Agriculture, Fisheries, and Forestry Sector to the Regional Economy - Yakup, Anggita Permata; Husain, Viona Pricilia (Gorontalo Development Review, 2024)
The purpose of this research is to determine the role of the agriculture, fisheries, and forestry sectors in increasing the regional economic growth of Gorontalo Regency. The analysis method used in this research is simple regression analysis to analyze the role of the agriculture, fisheries, and forestry sectors in increasing the economic growth of Gorontalo Regency. The research results show that the agriculture, fisheries, and forestry sector have been continuously increasing since 2010 to 2022, but the percentage of increase shows a downward trend. The increase in this sector indicates its ability to contribute to economic growth. However, the increase in economic growth in Gorontalo Regency is not optimal since some years experience a decline.